Food Security: Self–Sufficiency of Rice in Malaysia - Fatimah Mohamed Arshad; Emmy Farha Alias; Kusairi Mohd Noh; Muhammad Tasrif (International Journal of Management Studies, 2011)
Malaysia’s stance on food security is largely translated in terms of achieving self-sufficiency in rice production at about 65-70% of the local consumption. Since Malaysia does not have the comparative advantage in rice production, it implements a wide range of market interventions to achieve the intended level of rice production. The policy instruments include among others: guaranteed minimum price for paddy, price control, price and input subsidies and import monopoly. These interventionist instruments may not be sustainable in the long-term as they incur a high budgetary burden to the government, misallocation of resources and liberalization demand from WTO. The industry faces challenges in terms of land competition for urbanization and industrial uses and declining soil fertility due to heavy use of chemical fertilizer. This paper examines the influence of the fertilizer and the cash subsidies, as well as land conversion and fertility on the level of self-sufficiency in rice. A system dynamics model is applied to analyse the causal and feedback relationships of these variables in the paddy production system framework. The study shows that Malaysia may not be able to sustain the targeted self-sufficiency level without adequate R&D to address the production constraints particularly below-optimum productivity and the threats of climate change. The consumption of rice on the other hand continues to rise due to the increase in population.